Graphene surface plasmon sensor for ultra-low-level SARS-CoV-2 detection - Md. Mahbub Hossain; Muhammad Anisuzzaman Talukder (PLoS ONE, 2023)
Precisely detecting the ultra-low-level severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is crucial. The detection mechanism must be sensitive, low-cost, portable, fast, and easy to operate to tackle coronavirus disease 19 (COVID-19). This work proposes a sensor exploiting graphene surface plasmon resonance to detect SARS-CoV-2. The graphene layer functionalized with angiotensin-converting enzyme 2 (ACE2) antibodies will help efficient adsorption of the SARS-CoV-2. In addition to the graphene layer, ultra-thin layers of novel two-dimensional materials tungsten disulfide (WS2), potassium niobate (KNbO3), and black phosphorus (BP) or blue phosphorus (BlueP) used in the proposed sensor will increase the light absorption to detect an ultra-low SARS-CoV-2 concentration. The analysis presented in this work shows that the proposed sensor will detect SARS-CoV-2 as small as ∼1 fM. The proposed sensor also offers a minimum sensitivity of 201 degrees/RIU, a figure-of-merit of 140 RIU−1, and enhanced binding kinetics of the SARS-CoV-2 to the sensor surface.